Síntese e análise estrutural de complexos de Urânio e Vanádio com ligantes derivados da piridoxina - Ballin, Marco Aurélio (2009)
Uranyl and vanadyl complexes with ligands with oxygen and nitrogen donors atoms have been extensively reviewed and aroused remarkable interest on account their high stability but, a few complexes of piridoxine derived ligands have been reported in the literature. This lack was the inspiration to search new piridoxine derived ligands and uranyl and vanadyl complexes with the aim to explore their coordination behavior. The structural study in the solid state for the characterization of the crystalline structures of the complexes synthetized in this work was carried out with single crystal Xray diffractometry. The complex [UO2(hhmmb)(H2O)Cl]NO3×2H2O was obtained by recrystallization in dimethylsulfoxide of the product from the reaction of UO2(NO3)3.6H2O with the ligand {3-hydroxyl-5-(hydroxymethyl)-2-methylpyridine-4-yl-methylene}benzohydrazide (hhmmb) hydrochloride monohydrated in methanol. One ligand molecule, a water molecule and a chloride atom coordinate to the uranyl ion resulting a coordination number seven. The complex crystallizes in the triclinic system, space group P1. The complex [UO2(hhmmb)(CH3OH)Cl]NO3×CH3OH was attained through the reaction between UO2(NO3)3.6H2O and the ligand (hhmmb) hydrochloride monohydrated in methanol, where one ligand molecule, one methanol molecule and one chloride atom coordinate to the uranyl ion which presents also the coordination number seven. The complex crystallizes in the triclinic system, space group P1 as well. The complex [VO2(hhmmb)]×Py was achieved by the reaction between VO(acac)2 and the ligand hhmmb hydrochloride monohydrated in ethanol. One ligand molecule coordinate to the vanadyl ion giving a coordination number five. The complex crystallizes also in the triclinic system, space group P1. The complex [(UO2)2 (Pyr2dihid)(DMSO)4] was formed during the reaction between UO2(NO3)3.6H2O and the ligand Dihydrazide-bis(pyridoxine-1-yl) in methanol, where one ligand molecule and two dimethylsulfoxide molecules coordinate to each uranyl ion giving a coordination number seven. The complex crystallizes in the monoclinic system, space group P21/c.